PENGARUH MEDIA BIG BOOK TERHADAP KETERAMPILAN MEMBACA PERMULAAN SISWA KELAS II SD NEGERI LONRONG KABUPATEN GOWA - Mirwani Mirwani; Erma Suryani Sahabuddin; Rohana Rohana (Universitas Negeri Makassar, 2023)
This research is a type of quantitative research with a pre-experimental research design and a one-group pretest-posttest design that aims to determine students' beginning reading skills before and after the use of big book media. Data collection techniques were carried out using tests, observations, and documents. The data analysis techniques used were descriptive analysis and inferential analysis. Based on the results of descriptive statistics, it shows that students' beginning reading skills before using big book media obtained an average of 65.13 in the sufficient category, and their beginning reading skills after using big book media obtained an average of 87.20 in the excellent category. Based on the results of inferential statistics, the results obtained from tcount 5.630. Furthermore, compared with the t distribution table, for an error of 5% and dk = n-1 = 30-1 = 29, we obtained a value of 1.69913. The result of tcount is greater than ttable, so H0 is rejected and H1 is accepted. So it can be concluded that the use of Big Book Media affects the beginning reading skills of grade II students at SD Negeri Lonrong, Gowa Regency.